Penerimaan Kerja Berautomasi di Jabatan Tenaga Kerja Semenanjung - Abd. Rashid, Awang (2004)

(untitled)
This study examines the level of acceptance of work automation among the operational officers in Work Force Deparment of Malaysia (WFD). The objectives of this study is to investigate; i) The differences of the level of acceptance of work automation among the assessment officers based on demographic factors. ii) The relationship between the assessment officer's attitude with the level of acceptance of work automation, iii) The relationship between the assessment officers skill with the level of acceptance of work automation, iv) the relationship between the assessment officers' training with the level of acceptance of work automation, v) the relationships between the tops administration with the level of acceptance of work automation. A set of questionnaires containing 39 items using questions developed from 155 operational officers from Selangor, Wilayah Persekutuan, Negeri Sembilan, Kelantan dan Terengganu. Five hypotheses were constructed for this study. Statistical analysis used include frequency, mean, median, mode , standard deviation, t-Test, One-way Analysis of Variance and different level of the acceptance of indicates that; i) There are different level of acceptance of work automation among operational officers's base on demographics factors such as group of post, ages, and attend training/programme with exception on gender, academic qualification, tenure and having personal computer (PC). ii) Significant relationships between assessment officers attitude with the level of acceptance of work automation, iii) Significant relationships between assessment officers' in job training with the level of acceptance of work automation, v) not significant relationships between top management with the level of acceptance of work automation.